2005
DOI: 10.1038/sj.bmt.1704887
|View full text |Cite
|
Sign up to set email alerts
|

Intensive graft-versus-host disease prophylaxis is required after unrelated-donor nonmyeloablative stem cell transplantation

Abstract: Summary:Nonmyeloablative stem cell transplantation (NST) harnesses the graft-versus-tumor effect while minimizing regimen-related toxicity, and can result in donor chimerism and remission. Acute graft-versus-host disease (GVHD) and infections are major complications after sibling NST. Toxicity of unrelated-donor (UD) NST and the most appropriate GVHD prophylaxis in this setting remain poorly defined. We describe 25 patients who received UD-NST conditioned with fludarabine and cyclophosphamide. The first six pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…19 Reports have suggested that cyclosporine and MMF may not be sufficient to prevent GVHD in unrelated donors. 20 Rates for developing acute GVHD after RIC transplantation using tacrolimus or cyclosporine and methotrexate range from 12%–36% for patients with related and unrelated donors 21,22 Incorporation of alemtuzumab as GVHD prophylaxis is associated with a low incidence of acute and chronic GVHD 4 , however, many patients have persistent or progressive disease after transplantation suggesting that some element of the GVL effect has been compromised.…”
Section: Discussionmentioning
confidence: 99%
“…19 Reports have suggested that cyclosporine and MMF may not be sufficient to prevent GVHD in unrelated donors. 20 Rates for developing acute GVHD after RIC transplantation using tacrolimus or cyclosporine and methotrexate range from 12%–36% for patients with related and unrelated donors 21,22 Incorporation of alemtuzumab as GVHD prophylaxis is associated with a low incidence of acute and chronic GVHD 4 , however, many patients have persistent or progressive disease after transplantation suggesting that some element of the GVL effect has been compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Alemtuzumab is a monoclonal antibody against CD52, an antigen present on T cells as well as B cells and other antigenpresenting cells. It has been used both for ex vivo T cell depletion of stem cell grafts and has been administered directly to patients as part of conditioning regimens for alloHSCT [43,44,45]. Anti-CD52 therapy has been shown to reduce the risk of acute GVHD, although in one study engraftment was delayed, which may be due to the relatively long half-life of the antibody and thus a donor T cell−depleting effect.…”
Section: What Are the Relative Contributions Of Recipient Vs Host T mentioning
confidence: 99%
“…Anti-CD52 therapy has been shown to reduce the risk of acute GVHD, although in one study engraftment was delayed, which may be due to the relatively long half-life of the antibody and thus a donor T cell−depleting effect. In a more recent study of recipients of nonmyeloablative alloHSCT (see below), engraftment was achieved for all but one patient receiving alemtuzumab [44,45]. Because host antigenpresenting cells are also known to be critical to GVHD induction, alemtuzumab may work by blocking this key activation event [46].…”
Section: What Are the Relative Contributions Of Recipient Vs Host T mentioning
confidence: 99%
“…However, relapse rates tend to be high due to patient selection and the reduced intensity conditioning therapy, or in some cases the use of serotherapy (for example, alemtuzumab or antithymocyte globulin) resulting in in vivo T-cell depletion. 31,32 In these attenuated conditioning regimens, DLI has become increasingly important to maximize the GVL effect. [32][33][34][35][36][37] In addition, DLI is typically employed after NST when complete lymphohematopoietic chimerism is not achieved.…”
Section: After Non-myeloablative Sctmentioning
confidence: 99%